2005
DOI: 10.1007/s11205-004-6168-6
|View full text |Cite
|
Sign up to set email alerts
|

Well-Being in an Adult Swedish Population

Abstract: well-being, population-based,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 32 publications
(51 reference statements)
7
28
0
2
Order By: Relevance
“…Concerning environment we think that education together with income determine the status of a person that influences the quality of living conditions. Females had lower values of psychological status, this is consistent with other studies where women reported more negative emotions than men (Hansson, Hillerås, & Forsell, 2005;Tesch-Römer et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Concerning environment we think that education together with income determine the status of a person that influences the quality of living conditions. Females had lower values of psychological status, this is consistent with other studies where women reported more negative emotions than men (Hansson, Hillerås, & Forsell, 2005;Tesch-Römer et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Results of this study are in accordance to the results of Stevenson andWolfers (2009), Tesch-Römer, Motel-Klingebiel, andTomasik (2007), Costa et al (2001), Hansson et al (2005), and Tesch-Römer and Wurm (2006). Male students reported higher Islamic beliefs and thoughts than their female counterparts, as earlier mentioned, it is speculated that religion has a great impact on our thoughts, life style and behavior; and moreover, it can have effect on some aspects of our life, such as life satisfaction, happiness, self-esteem and well-being.…”
Section: Discussionsupporting
confidence: 91%
“…But some findings reported reverse results, in a study, Tesch-Römer, Motel-Klingebiel, and Tomasik (2007) revealed that females state more negative emotions than males. Similar findings were emerged from other studies (Costa, Terracciano, & McCrae, 2001;Feingold, 1994;Hansson, Hilleras, & Forsell, 2005;Nolen-Hoeksema & Rusting, 2003;Smith & Reise, 1998).…”
Section: Gender and Psychological Well-beingsupporting
confidence: 90%
“…This process is often called the ''hedonic treadmill.'' Recent studies using longitudinal data from the British Household Panel Study and other sources indicate that such treadmill effects are not inevitable (see, e.g., Hansson 2009). has been largely neglected in studies of subjective well-being.…”
Section: Conclusion: Government Performance and Life Satisfactionmentioning
confidence: 99%